From Crisis to Growth: Parental Resilience Among Indonesian Muslim Mothers of Children with Down Syndrome—An Interpretative Phenomenological Analysis - Gilang Tri Prayogo Yusuf; Aaisyah Hafshah Rafie:; Aisyah Ismiranti Alfattah Putri; Abdallah Al Ahmad Wahab; Ahmad Fathih Fakhir; Gyanesh Kumar Tiwari (Universitas Mercu Buana Jakarta, 2026)
Down syndrome presents Indonesian parents with complex caregiving responsibilities that create emotional strain, stigma, and persistent anxiety. While parental stress is well-documented, how parents develop resilience as a dynamic, relational process remains poorly understood. This study explored parental resilience among Indonesian Muslim mothers of children with Down syndrome in Makassar using Interpretative Phenomenological Analysis (IPA). Seven mothers (aged 30–45 years) with at least two years of caregiving experience, recruited through a Down syndrome parent support organization in Makassar, underwent semi-structured interviews. Six superordinate themes emerged: acceptance as a temporal process, patience (sabar) as active emotional regulation, identity reframing and agency, family and community support, spiritual meaning-making, and time management and priorities. Resilience developed through three phases: crisis and disorientation, adaptation and learning, and consolidation and growth. Results indicate that resilience emerges through relational and temporal dimensions, mediated by family support, community engagement, and culturally embedded meaning-making. To the best of the authors' knowledge, this is the first IPA study of parental resilience among Indonesian Muslim mothers of children with Down syndrome, integrating temporal, relational, and Islamic spiritual dimensions within a single analytical framework. Findings underscore the importance of culturally-responsive, family-centered interventions recognizing resilience as a relational and temporal phenomenon grounded in lived experience.